Desenvolvimento de metodologias de divulgação científica por meio de pesquisa e produção de mangás - Iwata, Adriana Yumi (Universidade Federal de São Carlos, 2020)
Science communication can be defined as any practice that proposes to spread the science to the public, with the purpose of arousing interest and motivation in science, as well as informing and disseminating scientific knowledge. This work did an analysis of the state of the art in the production of comic books that introduce scientific topics – science comics - and its reach as entertainment and information media, as well as discussing its potential to teach and /or disseminate science. The objectives of this work were the elaboration and analysis of science communication methodologies involving the use of comics, especially using the Japanese sequential art - manga. The methodology used comprised a series of non-formal activities divided into two lines of research: production of comic books made by the researcher and production of comics by the public, and the scientific theme used in these comics produced focused on the theme of glass. The results obtained showed the potential of comic books as a tool for science communication, both as reading material as an activity that promotes creativity and the development of stories, and the research was successful in developing and validating a methodology using comics as a tool for science communication, using glass as a scientific theme. Activities involving science and art has the possibility to increase the interest of the general public regarding scientific subjects, presenting the science in a different and playful way.
Development of science communication methodologies through research and manga production
Keywords: Divulgação científica; Atividade lúdica; Produção de HQs; Ciência-Arte; Vidros; Science communication; Playful activities; Comics production; Science-Art; Glass; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM